Panel Data Analysis on Income Tax Progressivity and Gini Coefficient - Parsons, Brandon; Naghshpour, Shahdad (Journal of Applied Business and Economics, 2022)
The research explores personal income tax progressivity as a mechanism to reduce income inequality. In the personal income tax progressivity model with data from 1988-2005, the unbalanced panel has up to 103 countries with 1,528 observations. The unbalanced panel uses Driscoll and Kraay standard errors to adjust for nonparametric heteroscedasticity autocorrelation. The researchers test the top, marginal, and average personal income tax rate progressivity. In the full panel, the top, marginal and average rate of personal income tax progressivity are all statistically significant. The models also explore differences in results based on income level. Key findings include the average rate of personal income tax progressivity is statistically significant in the more panels than the marginal rate of income tax progressivity or the top marginal rate. Both the net and market Gini coefficients tend to have similar statistical significance results which may suggest equality promoting policies may cause structural changes in the economy that lead to higher pre-tax incomes for lower-income individuals.